NEO MODERNISME ISLAM INDONESIA: WACANA KEISLAMAN DAN KEBANGSAAN NURCHOLISH MADJID - -, Suryani (Departemen Ilmu Politik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2016)
Neo modernism emerged as a critical discourse face the phenomenon of modernist Islamic thoughtÂ that emphasizes reason and ratio in view of the existence of religion in a struggle and debate ideasÂ discourse on Islam and society. In the neo modernism discourse, the phenomenon of religiousÂ exclusivity becomes a very important study. Exclusive theology is used by some hard-line IslamicÂ groups to judge other religions or other Islamic groups that are not inline with Islam that theyÂ believe to be the real truth. Neo modernism evolved to respons this religious exclusivity and theÂ religious inclusivity comes to make a new discourse on Islam which has the main idea of anÂ understanding of the universal message delivered by God not only to one particular religion butÂ also to other religions in the scriptures each. The efforts to avoid subjectivity of religion andÂ promote objectivity in the social sphere in Nurcholish Madjidâs thought will not reduce theÂ religious existence, but will make it more effective and elegant can also be easily accepted byÂ modern society without suspicion.